Income-related inequality in health and health-related behaviour: exploring the equalisation hypothesis. Issue 7 (11th March 2014) - Vallejo-Torres, Laura; Hale, Daniel; Morris, Stephen; Viner, Russell M
Abstract : Background: Previous studies have found the socioeconomic gradient in health among adolescents to be lower than that observed during childhood and adulthood. The aim of this study was to examine income-related inequalities in health and health-related behaviour across the lifespan in England to explore 'equalisation' in adolescence. Methods: We used five years of data (2006–2010) from the Health Survey for England to explore inequalities in six indicators: self-assessed general health, longstanding illness, limiting longstanding illness, psychosocial wellbeing, obesity and smoking status. We ran separate analyses by age/gender groups. Inequality was measured using concentration indices. Results: Our findings for longstanding illnesses, psychosocial wellbeing and obesity were consistent with the equalisation hypothesis. For these indicators, the extent of income-related inequality was lower among late adolescents (16–19 years) and young adults (20–24 years) compared to children and young adolescents (under 15 years), mid- and late-adults (25–44 and 45–64 years) and the elderly (65+ years). The remaining indicators showed lower inequality among adolescents compared to adults, but higher inequality when compared with children. Conclusions: Our work shows that inequalities occur across the life-course but that for some health issues there may be a period of equalisation in late adolescence and early adulthood.